A Friedländer route to 5, 7-diazapentacenes. Issue 14 (12th January 2018) - Lunchev, Andrey V.; Hendrata, Vincent C.; Jaggi, Aparna; Morris, Samuel A.; Ganguly, Rakesh; Chen, Xiaoxuan; Sun, Handong; Grimsdale, Andrew C.
Abstract : New 5, 7-diazapentacene-based materials have been made by means of a Friedländer reaction, which could be promising candidates for optoelectronic applications. Abstract : A route to compounds with a 5, 7-diazapentacene skeleton has been established involving a Friedländer reaction. A diaminodiketone8 has been made by a novel method and reacted with cyclohexanone to prepare an octa-hydro-5, 7-diazapentacene7a and with tetralone to produce a dibenzotetrahydro-5, 7-diazapentacene7b . Reaction of the diaminodiketone with a diarylethanone followed by oxidation gave a tetrabenzo-5, 7-diazapentacene18b . Compound7b undergoes solid-state dimerization during single-crystal X-ray analysis. These materials possess lower frontier orbitals than pentacene and show strong absorption and fluorescence which is affected by the presence of acid. In particular18b shows a remarkable colour change in solution upon addition of acid. These results suggest that suitably functionalised 5, 7-diazapentacenes could be promising candidates for optoelectronic applications.